Analisis Pengembangan Potensi Dan Kendala Yang Dihadapi Umkm Berbasis Ekonomi Kreatif Dalam Meningkatkan Daya Saing Di Kabupaten - Putra, Rizki Nur Syafril Eka; Samsuki, Samsuki (Jurnal Ilmiah Wahana Pendidikan, 2024)
The implication of this research is that by referring to the results of this research, it contributes to existing studies by analyzing the potential development and obstacles faced by creative economy-based MSMEs in increasing competitiveness in Sumenep Regency. The research used in this research uses quantitative methods. Research methods that can be chosen by researchers are in accordance with the type and nature of research, population and sampling techniques, research data sources, data collection techniques in the form of questionnaires, interviews, documentation on MSME actors in Sumenep Regency. This research analysis will later lead to the development of the potential and obstacles of Creative Economy-based MSMEs in increasing competitiveness in Sumenep Regency.